Evaluation of Prayer Windows with Inscriptions Located Around the Mausoleum of Eyup Sultan - Saliha Tanık; Aliye Öten (Cumhuriyet İlahiyat Dergisi)

(untitled)
Prayer windows are architectural elements of various forms that are opened on the surface of the walls of mosques, tombs, lodges, cemeteries, or treasuries in the direction of people's passage and usually have inscriptions. The prayer windows opened on the body or courtyard wall of the tombs exhibit an imposing appearance in a way to attracts people's attention. In front of such windows, in the presence of the deceased, prayers and requests are made to Allah for his sake. Eyüp Sultan Mosque and Mausoleum are places where crowds of people gather on holy days of religious importance such as Friday. The prayer windows were made near the graves of common people who were not considered religious leaders, even if they had a high social status, and buried in the cemeteries around Eyüp Sultan Tomb, and in the openings in the enclosure wall of these cemeteries, have been the subject of our study with their inscriptions ending with the request for Fatiha. It is understood that the prayer windows, which are in the position that constitutes the connection of the treasuries with the street, were opened to request prayer by attracting the attention of people passing by to visit mosques and tombs. We have tried to determine the place of prayer windows in the discipline of art history since they were not applied in the first period of Islam but were an elegant practice that emerged especially in the Ottoman period and had not been studied before. We have endeavored to determine the effect and reflection of the visit tradition shaped by the Ottoman period adherents of the Islamic religion on Islamic art throughout this subject. In our research, we have tried to find the first information about prayer windows. We have tried to determine the place of prayer windows in the discipline of art history since they were not applied in the first period of Islam but emerged especially in the Ottoman period and have not been studied before. We have endeavored to determine the effect and reflection of the visiting tradition shaped by the Ottoman period followers of the Islamic religion on Islamic art throughout this subject. In the first part of our research on prayer windows, Eyüp Sultan Mosque and Tomb in terms of the tradition of visitation in Islam; in the second part, the purpose and importance of the construction of prayer windows and the evaluation of these building elements in terms of form, material-technique, writing, ornamentation, and identity are discussed. In this process, the necessary permissions and usable data were obtained from the Directorate of Tombs, Istanbul Directorate of Cemeteries, and the General Directorate of Foundations Istanbul 1st Regional Directorate for the examination of 11 windows that we identified in the cemeteries around Eyüp Sultan, and the measurements of the windows were taken in a process of approximately two weeks. Within the framework of the necessary security measures, tools such as ladders and tripods were used to take the correct measurements of the high windows. The stumpage technique was applied to the inscriptions and high-relief decorations. There were some difficulties in measuring and photographing the windows due to the location of the land and the passage point of the people. The photographs were taken in detail and shared as general views and only general views were used in order not to exceed the volume of the article. The gravestones related to the subject in the background of the windows were also identified one by one by scanning the whole of the treasuries. With the data obtained because of measurement and photography, the windows were drawn with the AutoCAD program in about one and a half months. Sources on the subject were researched in many libraries in Istanbul and Ankara and on the net and collected in an average of one month. In the evaluation phase, the inscriptions of each prayer window and the associated tombstones were read and analyzed, and inferences about the art and the master were made with the signatures of the artisans on the inscriptions. In terms of art history, subheadings were opened according to the forms of the windows, and definitions were made. As an example of an application specific to the Ottoman period in Islamic architecture and art, our main aim has been to bring the prayer windows opened in the cemeteries around Eyüp Tomb to the discipline of Art History in the context of form, ornamentation, writing, and death. The text created by evaluating all the data is the result of a meticulous, comprehensive, and long-term process. With this study, it has been attempted to understand the Muslim view of death and the cultural heritage developed within this framework based on the building elements in question.